Background method of radar detection of a moving small target object in the task of classifying active radars. (March 2020) - Anikin, A S; Khristenko, A V; Ochirtarov, A V
Abstract: The article deals with the classification of radar equipment based on two features: on the location of the receiving and transmitting points in space, as well as by the method of generating an informative signal at the receiving point. The most significant parameters in the development of a moving target detector near the underlying surface have been observed.